PENINGKATAN KEMAMPUAN MEMPREDIKSI MELALUI PENERAPAN MODEL PEMBELAJARAN INTERACTIVE DEMONSTRATION PADA SISWA KELAS XI - Khoirul Annisa; Slamet Santosa; Suciati Suciati; Suratno Suratno (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2018)
The purpose of the research was improveability to predictthrough interactive demonstration learning of graders XI which includes 32 students. The research was a classroom action research that refer to Kemmis and Mc Tggart model (2005). The research was performed within two cycles which consists of planning, acting, observation, and reflection stage. Action in the research used interactive demonstration learning. Theresearch data includes assessment result of ability to predict. Ability to predict was assessed by essay test and observation of ability to predict.The validity of data used technique of triangulation method. The research data was analyzed by qualitative descriptive.Known from Pre-Cycle results that students’s ability to predict was 32,18%. Indicator of the success of action was improvement of students’s ability to predictin Cycle II. Results of the research showed that ability to predict improved 66,41%in Cycle II. The improvement of students’s ability to predictwas facilitated by interactive demonstration model.Conclusion of the research was showed that student’s ability to predict and curiosity improved 66,41%through interactive demonstration learning. Keywords:       ability to predict, interactive demonstration learning